The Influence of Time Budget Pressure, Time Deadline Pressure and Work Stress on Audit Quality of External Auditor - Dodik Juliardi Iksan (Integrated Journal of Business and Economics (IJBE), 2023)
The purpose of this study was to  try  the  goods of time pressure, deadline pressure, and work pressure on  test quality among PAF observers in Malang City. The  logical model  exercised is a  multitudinous retrogression  dissection where the dependent variables are time pressure( X1), deadline pressure( X2), job pressure( X3) and the independent variable is  test quality( Y). The study population was his PAF accountants in Malang, totaling 86. The sample  exercised  comported of her 52 repliers,  utilizing a accessible sample of his eight account  enterprises( PAF) in Malang  megacity. A Likert scale( 1- 4) questionnaire is  exercised for the  dimension. Data source is primary. This study shows that time pressure, deadline pressure, and job pressure don't affect the quality of  foreign  checkups.  terminations of this study are that the questionnaire  effects don't  give his 100 valid comebacks due to lack of  management, that the repliers are  pacified by  youthful observers, and that the study  effects are in this range. Secondly, it can not be generalized to  multitudinous regions in Indonesia. Research will be limited to a  defined bone in Malang City.